Maternal Complications Following Open and Fetoscopic Fetal Surgery: A Systematic Review and Meta-analysis. Issue 8 (August 2019) - Sacco, Adalina; Van der Veeken, Lennart; Bagshaw, Emma; Ferguson, Catherine; Van Mieghem, Tim; David, Anna L.; Deprest, Jan
Abstract : (Abstracted from Prenat Diagn 2019;39(4):251–268) Fetal therapy options have expanded, and surgery on the fetus, placenta, or cord is now relatively common in tertiary-level fetal medicine units. Fetal therapy is almost exclusively offered to mothers who are healthy themselves, yet fetal surgery poses risks to the mother not only during the procedure itself but also during the remainder of the index pregnancy, potentially during any future pregnancies and throughout the woman's entire life.